Novel controllable degradation behavior and biocompatibility of segmented poly–ε–caprolactone in rats. (May 2019) - Yang, Jean-Dean; Shu, Yi-Ting; Jia, Hsi-Wei
Abstract: Bioresorbable polymers have multiple clinical applications; however, the reaction methods required for their synthesis generally require harsh reaction conditions and long reaction times. This study uses a new conceptual molecular control method that links poly–ε–caprolactone (PCL) diols of differing molar mass with an aliphatic diisocyanate as a coupling agent for polymerization to develop a new type of segmented polycaprolactone (SM-PCL) material. Relative to the polymerization of typical high molecular weight polyester materials, this polymerization process only requires ordinary pressure and low temperature to yield product with sufficiently high molecular weight. The results of in vitro cytotoxicity and in vivo implantation assays show that the newly synthesized SM-PCL exhibits excellent biocompatibility. In addition, in vivo degradation analyses demonstrate that the porous SM-A material was nearly completely degraded at 6 months after implantation in rat tissue (P < 0.01), whereas porous PCL homopolymer was only degraded to 53.25% of the initial molecular weight even after 12 months. The study indicated that the degradation rates of porous and solid thin film SM-PCL were higher than those of PCL homopolymer and that its degradation behavior could be controlled. Moreover, the material did not result in significant adverse pathological reactions and has good tissue compatibility. For clinical application, this material may therefore be suitable as a carrier for controlled drug release or as an artificial material for soft tissue repair. Highlights: Novel molecular control method for new porous and solid thin film SM-PCL materials. DABCO/Sn(II)Oct complex catalyst system and Soxhlet extraction gave SM-PCL Mw > 70 kDa. SM-PCLs exhibited biocompatibility in vitro and in a rat implantation model in vivo. Modulating SM-PCL molecular composition yielded high, controlled degradation rates. These next-generation materials may have tissue repair or drug release applications.